Sources and doses of aluminum in experiments with rice in nutrient solution - Freitas, Lucas B. de [UNESP]; Fernandes, Dirceu M. [UNESP]; Maia, Suelen C. M.; Moniz, Arianne [UNESP]; Mazziero, Beatriz G. [UNESP]; Steiner, Fabio (Univ Federal Campina Grande, 2019)
The aluminum source to produce toxicity in upland rice in nutrient solution experiments is not yet well established, althought the aluminum potassium sulfate has been utilized source to produce aluminum toxicity. However, in recent studies have used aluminum chloride. The aim of this study was to evaluate the capacity of aluminum sources and doses to produce toxicity in upland rice plants grown in nutrient solution. The experiment was arranged in a block randomized design, in a 2 x 5 factorial scheme and four repetitions. The treatments were two aluminum sources (aluminum potassium sulfate - AlK(SO4)(2).12H(2)O and aluminum chloride - AlCl3.6H(2)O) and five aluminum doses in nutrient solution (0, 370, 740, 1100 and 1480 mu mol L-1). The experiment was conducted in a greenhouse in Botucatu city, Sao Paulo state, Brazil, starting in April 2012, and was carried out for 56 days from transplanting of the seedlings. Using aluminum chloride, the rice plants show lower production of root and total dry weight, area and root volume, medium and thick root length, potassium and sulfur contents and accumulations. Using aluminum potassium sulfate, there are lower aluminum activity and availability, besides the formation of large amount of aluminum compounds non-toxic to the plants (aluminum sulfate) in the nutrient solution. The aluminum doses between 1100 to 1480 mu mol L-1, corresponding to aluminum activity of 336.8 to 429.0 mu mol L-1 of aluminum chloride as source, are more effective to produce aluminum toxicity in upland rice plants grown in nutrient solution.
Keywords: Oryza sativa; ionic activity; Visual Minteq; root length